Paint thinner exposure inhibits testosterone synthesis and secretion in a reversible manner in the rat - Yilmaz, Bayram; Canpolat, Sinan; Sandal, Suleyman; Akpolat, Nusret; Kutlu, Selim; Ilhan, Necip; Kelestimur, Haluk (Pergamon-Elsevier Science Ltd, 2006)
Occupational exposure and sniffing of toluene-based organic solvents is an important public health problem. In this study, we have investigated the effects of paint thinner inhalation on testosterone synthesis and secretion in the male rat. A contrl group inhaled normal air ventilation. The remaining animals were divided into three groups and exposed to paint thinner in a glassy cage for 15 and 30 days (2 h/day). A group of rats was allowed to recover for 15 days after 30 days of exposure. Toluene concentration (the largest constituent in thinner, 66%) was set at 1500 ppm in the inhaled air. At the end, all animals were decapitated and blood samples obtained. Testes and seminal vesicles were removed and weighed out. Serum total testosterone levels were determined by chemiluminescence enzyme immunoassay. Testicular tissue specimens were processed for semi-quantitative evaluation of immunohistochemical testosterone staining and light microscopy. Intensity of immunostaining was evaluated on a scale between 0 (no staining), I (minimal), 2 (mild), 3 (moderate) and 4 (strong staining). Serum testosterone levels (ng/ml) were decreased by 15-day (3.31 +/- 0.61) and 30-day (1.17 +/- 0.54, p < 0.02) thinner exposure compared to the controls (3.91 +/- 1.03). Another group of rats exposed to thinner for 30 days and then allowed to recover for a period of 15 days had significantly elevated levels of testosterone values (3.77 +/- 1.1; p < 0.05). Immunohistochemical testosterone staining of the cytoplasm of Leydig cells was moderate (3+) and mild (2+) in 15 and 30 days thinner inhalation groups, respectively. Strong staining (4+) was restored following the recovery period. Testicular weight was significantly reduced in all test groups compared to the control values (p < 0.01). Diameters of seminiferous tubules were significantly decreased in the solvent exposed groups with enlarged connective tissue. The present findings suggest that paint thinner inhalation inhibits testosterone synthesis and secretion by a direct action on the Leydig cells in a reversible manner. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: paint thinner; testosterone; Leydig cells; immunohistochemistry; testis and rat